Kualitas, Kemampuan Implantasi dan Viabilitas in-vivo Embrio Mencit (Mus muculus) Galur Swiss Webster Setelah Pembekuan Dengan Metode Vitrifikasi - Madihah Madihah; Hartanti Kusumaningtyas; Arief Boediono; Sony H. Sumarsono (Universitas Atma Jaya Yogyakarta, 2006)
Reproductive technologies including in vitro fertilization (IVF), embryo manipulation, gamete and embryo freezing, thawing and embryo transfer were rapidly developed. Vitrification is an embryo freezing technique that is the most developed. In this experiment, we vitrified mouse embryos and then examined the embryos i.e: (i) the quality of the embryos after thawing, (ii) the implantation rate of the embryos and (iii) viability of the embryos in vivo. Morulae and blastocycsts were collected from female mice that were pregnant a day 3,5. The embryos were equilibraten in mPBS +10% etilene glycol. Vitrification was carried out by using VABEDS medium, containing 6-10 embryos that were dropped into a tip of a straw, then frozen in liquid nitrogen for 24 hours. Thawing was carried out by flushing the embryos using mPBS suplemented with 0.5, 0.25, 0.1 and 0 M sucrose. After being incubated in M2 medium at 37oC for 1-2 hours, the recovery embryos were then transferred into the uteri of day 2.5 of pseudopregnat females. The females were then sacrificed at day 16 of gestation and the total implantaion, total life and death fetuses, as well as resorpted embryos, were taken as data. The results showed that vitrification significantly (p<0,05) reduced the quality of the embryos, as well as their implantation rate and the viability of the fetuses, which may be caused by the unoptimal combination of the cryoprotectant in the vitrification medium, temperature and exposure time during vitrification.